Integrative-Islamic Learning Model for Hadith Education through Wawacan Panganten Tujuh - Hidayatulloh, Deden Syarif (International Journal of Nusantara Islam, 2024)
This research is motivated by the importance of developing a hadith learning model that is relevant to the local cultural context, especially in Indonesia, which is rich in cultural diversity. Wawacan Panganten Tujuh as an Islamic-based literary manuscript from Sundanese culture was chosen as a potential teaching material to enrich the hadith learning method. The integrative-Islamic pedagogy approach is used to integrate cultural values and Islamic teachings in the learning process, which is expected to increase students' understanding of hadith as well as strengthen their appreciation of local culture. The results of the study show that the learning model developed is not only effective in improving the understanding of hadith, but also provides a meaningful learning experience through the active involvement of students in their cultural context. This model combines the exploration of Sundanese culture with the teachings of hadith, allowing students to understand Islamic teachings in a more in-depth and contextual way. Unlike previous studies that only emphasized cultural aspects or content analysis, this study presents a holistic approach that integrates both aspects in a single learning model. The conclusion of this study confirms that the hadith learning model based on Wawacan Panganten Tujuh through an integrative-Islamic pedagogy approach is able to answer the needs of contextual Islamic education in Indonesia. The contribution of this research expands the scope of cultural-based Islamic education literature, although its implementation is still limited to certain areas. Further research is expected to develop similar models for other cultures and analyze the impact of their application more broadly in Islamic education